Egypt is Thinking About the Future - V. A. Isaev; A. O. Filonik (Мир новой экономики)
For decades, Egypt has been developing under the pressure of unfavorable factors that consistently complicate the work of its reproductive mechanisms, the functioning of the market and other institutions, and result in a series of economic turmoil, social tensions, and political upheavals. In certain periods, the country managed, under favorable circumstances, to mobilize its capabilities to temporarily offset and compensate for the negative influence of internal and external factors and even demonstrate signs of some macroeconomic stability. But the general trend, characteristic of and inherent in an economy developing in harsh conditions, did not give a chance to stay on a more or less constant course for a long time. At the beginning of the second decade of the new century, violent popular uprisings and demonstrations actually led the country to a serious crisis. Its echoes are still felt today, and they carry an element of extremely undesirable destabilization for the largest state in the region. Egypt has historically retained the status of a regional power, no longer the only one, but involved in almost all economic and political initiatives and processes developing in the Arab region, playing an important role in them, which, naturally, should be supported by the corresponding economic potential.